A simple and efficient sequential electrokinetic and hydrodynamic injections in micellar electrokinetic chromatography method for quantification of anticancer drug 5‐fluorouracil and its metabolite in human plasma. (20th December 2020) - Semail, Nadhiratul‐Farihin; Noordin, Siti Salmah; Keyon, Aemi Syazwani Abdul; Waras, Maisarah Nasution; Saad, Bahruddin; Kamaruzaman, Sazlinda; Mohamad Zain, Nur Nadhirah; Azizi, Juzaili; Aziz, Mohd Yusmaidie; Yahaya, Noorfatimah
Abstract: A simple and sensitive preconcentration strategy using sequential electrokinetic and hydrodynamic injection modes in micellar electrokinetic chromatography with diode array detection was developed and applied for the separation and determination of anticancer agent, 5‐fluorouracil and its metabolite, 5‐fluoro‐2′‐deoxyuridine, in human plasma. Sequential injection modes with increased analyte loading capacity using the anionic pseudo‐stationary phase facilitated collection of the dispersed neutral and charged analytes into narrow zones and improved sensitivity. Several important parameters affecting sample enrichment performance were evaluated and optimized in this study. Under the optimized experimental conditions, 614‐ and 643‐fold and 782‐ and 803‐fold sensitivity improvement were obtained for 5‐fluorouracil and its metabolite when compared with normal hydrodynamic and electrokinetic injection, respectively. The method has good linearity (1–1, 000 ng/ml) with acceptable coefficient of determination ( r 2  > 0.993), low limits of detection (0.11–0.14 ng/ml) and satisfactory analyte relative recovery (97.4–99.7%) with relative standard deviations of 4.6–9.3% ( n = 6). Validation results as well as the application to analysis of human plasma samples from cancer patients demonstrate the applicability of the proposed method to clinical studies.